2018
DOI: 10.1016/j.resuscitation.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord milking in preterm neonates requiring resuscitation: A randomized controlled trial

Abstract: Clinical trials registry -India CTRI/2015/01/005436, www.ctri.nic.in.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…When compared with ICC, intact cord milking was not associated with an increased risk of IVH (grade 3 or more) (RR 0.69 (95% CI 0.38 to 1.24), p=0.22, I 2 =0%, 8 studies19 21 22 24 27–29 32 (n=598)) (figure 3). Only one study on cut UCM reported on this outcome30 and found no difference (online supplementary table 4).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…When compared with ICC, intact cord milking was not associated with an increased risk of IVH (grade 3 or more) (RR 0.69 (95% CI 0.38 to 1.24), p=0.22, I 2 =0%, 8 studies19 21 22 24 27–29 32 (n=598)) (figure 3). Only one study on cut UCM reported on this outcome30 and found no difference (online supplementary table 4).…”
Section: Resultsmentioning
confidence: 91%
“…Meta-analysis found no significant effect on mortality with UCM when compared with DCC (RR 0.93 (95% CI 0.55 to 1.55), p=0.77, I 2= 0%, 4 studies8 16–18 (n=890)) (figure 2) .There was no significant difference in mortality between the I-UCM and ICC groups (RR 0.85 (95% CI 0.49 to 1.46), p=0.56, I 2= 27%, 10 studies19 21–24 27–29 31 32 (n=698)) (figure 3). Cut UCM did not have a significant effect on mortality when compared with ICC (RR 1.00 (95% CI 0.35 to 2.90), p=1.00, I 2 =34%, 2 studies26 30 (n=260)) (online supplementary table 4).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, there is an urgent need for high quality evidence to compare the use of UCM to ICC in infants that need resuscitation. Two recent trials from India demonstrated that it is feasible to study term and preterm who are depressed at birth ( 54 , 55 ). We need to determine if umbilical cord milking provides a superior placental transfusion and improves neonatal outcomes compared to current approaches.…”
Section: Discussionmentioning
confidence: 99%